IDENTIFIKASI MASALAH APLIKASI TEKNOLOGI PENGOLAHAN AIR PAYAU DENGAN SISTEM RO DI KABUPATEN REMBANG DAN CARA MENGATASINYA - Rahardjo, Petrus Nugro (Center for Environmental Technology, 2010)
A brackish water treatment process technology based on reverse osmosis principle has been applied in an Islamic school community Ã¢â‚¬Å“RaudlatuttalibinÃ¢â‚¬Â, Rembang, since July 2008. Production capacity of the water treatment plant was designed 10M3 of drinking water per day. After running the system for one and a half years, a lot of problems were consecutively appearing untill the end of March 2010. This identification activity clarified all problems in detail and explained how to solve them. They are not only technical problems, but also social and cultural problems of the community. To solve them it must be started from increasing the capability of operators and applying the clean production concept. Finally by changing all the technically broken spareparts and running the RO unit system properly, they will be guaranteed to be able to produce good quality of drinking water. Ã‚Â Keywords : water treatment plant, reverse osmosis, technical & social problems.